2010
DOI: 10.5920/mhldrp.2010.72159
|View full text |Cite
|
Sign up to set email alerts
|

Older Carers and Adults with Learning Disabilities: Stress and Reciprocal Care

Abstract: People with a learning disability have an increased longevity. The majority of adults with a learning disability live with their parents which means that many of these parents are themselves elderly people. For the first time more adults with learning disability are outliving their parents. This paper presents some of the findings of a qualitative case study using interviews and focus groups with 24 carers and 14 adults with learning disabilities. It explores older carers' perceptions of stress and experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…As this study suggests, the caregiving relationship evolves into a reciprocal caring relationship overtime involving both tangible and emotional support. Similar findings have been reported elsewhere (Grant, 1986; Walker & Walker, 1998; Walmsley, 1996; Prosser, 1997; Williams & Robinson, 2001; Foundation for People with Learning Disabilities, 2003; Bowey and McGlaughlin, 2005; Knox & Bigby, 2007; Gant, 2010; Perkins & Haley, 2013) describing how people with intellectual disabilities living with ageing family members assume caring responsibilities and provide support ranging from help with shopping, to relatively heavy domestic tasks such as changing beds and the provision of intimate personal care including assistance with medication.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As this study suggests, the caregiving relationship evolves into a reciprocal caring relationship overtime involving both tangible and emotional support. Similar findings have been reported elsewhere (Grant, 1986; Walker & Walker, 1998; Walmsley, 1996; Prosser, 1997; Williams & Robinson, 2001; Foundation for People with Learning Disabilities, 2003; Bowey and McGlaughlin, 2005; Knox & Bigby, 2007; Gant, 2010; Perkins & Haley, 2013) describing how people with intellectual disabilities living with ageing family members assume caring responsibilities and provide support ranging from help with shopping, to relatively heavy domestic tasks such as changing beds and the provision of intimate personal care including assistance with medication.…”
Section: Discussionsupporting
confidence: 88%
“…This is known as "reciprocal caring" or "mutual support." The interdependency within these families, where the person with an intellectual disability adopts a caring role, is common and there is a growing awareness of the importance of reciprocal caring relationships (Grant, 1986;Perkins & Haley, 2013;Walker & Walker, 1998) as well as the needs of older people with intellectual disabilities and their ageing families in policy (DoH, 2001(DoH, , 2003Foundation for People with Learning Disabilities, 2003, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…While ageing parents continue to care for their offspring in the face of challenges related to old age, there is evidence that many parents benefit from help, assistance and companionship provided by their son/daughter with an intellectual disability (Gant, 2010). A recent systematic review of literature on the experiences of carers aged 75 years and over reported that some studies suggested caring was potentially less challenging for older carers as they adapt to their role (Greenwood & Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, adults with intellectual disabilities are living into old age in significant numbers, and outliving their parents. The emphasis of UK policy recommendations is on community- and family-based initiatives for support of adults with intellectual disabilities, which is evident in the literature indicating the majority of people with intellectual disabilities in the United Kingdom continue to live at home with their families (Cairns et al 2013; Gant, 2010). Adults with intellectual disabilities are less likely to have a spouse/partner or children who may be called upon to care for them in later life (Ryan et al, 2014), and family carers (usually parents) are themselves experiencing continuing longevity.…”
Section: Introductionmentioning
confidence: 99%